전망이론과 김정은 시기 북미관계: 2012~2023 - 황지환; Jihwan Hwang (한국과 국제정치, 2024)
김정은은 지난 10여년 동안 초강대국 미국에 도전하며 변화무쌍한 대외정책을 펼쳐왔다. 김정은은 집권이후 미국에 대립적인 정책을 추진하다가 왜 2018년 갑자기 협상과 외교로 전환하고 북미정상회담을 성사시켰을까? 김정은은 왜 2020년 이후 또 다시 대립적인 대미정책으로 돌아갔을까? 김정은은 왜 단일하고 일관적인 핵정책과 대미정책을 유지하지 않았을까? 이 글은 전망이론의 위험(risk) 개념을 통해 김정은 시기 북한의 핵정책과 북미관계 변화를 설명한다. 김정은은 대미정책 옵션의 상대적 위험성을 어떻게 인식했을까? 그 위험은 김정은의 의사결정 과정에 어떤 영향을 미쳤을까? 북핵 위기와 미국의 대북 적대시 정책이라는 초기조건은 변하지 않았는데, 왜 그의 정책 선택은 변화했을까? 대외정책의 모든 선택은 어느 정도 위험을 수반할 수밖에 없다. 따라서 각 상황의 기준점과 상대적 위험 정도를 평가하는 것은 정책 분석에 중요하다. 이 글은 김정은의 정책선택이 그의 기준점 인식과 위험수용 경향에 의해 변화함을 설명한다. For the past decade or so, Kim Jong Un has pursued changing foreign policies, challenging the United States, a global superpower. Why did Kim suddenly change his policy toward the United States and conclude the historic U.S.-DPRK summit in 2018 after pursuing a confrontational policy? Why did Kim return to his confrontational policy in 2020? Why did Kim shift his policy from confrontation to negotiation and back to confrontation without maintaining a consistent foreign policy toward the United States? This article draws on the concept of risk in prospect theory and explains changes in Kim Jong Un’s nuclear policy and U.S.-DPRK relations. How did Kim recognize the relative risk of each policy option toward the United States? How did the risks affect Kim’s decision-making process? Why did Kim’s policy choices change although the initial conditions of the North Korean nuclear crisis and U.S. hostile policy toward North Korea did not change? Every choice of foreign policy involves some risk. Therefore, it is important to recognize the reference point and evaluate the relative risk of each policy choice in analyzing Kim’s policy changes. The North Korean policy changes depend on changes in Kim’s perception on the reference point and his risk-taking attitude.